1994
DOI: 10.1111/j.1365-2419.1994.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of juvenile sockeye salmon (Oncorhynchus nerka) migrations in the Strait of Georgia, British Columbia

Abstract: Previous research has documented two main migratory routes of juvenile sockeye salmon (Oncorhynchus nerka) through the Strait of Georgia, British Columbia, Canada, and large interannual variability in marine survival rates of the Chilko Lake stock. Simulation models were used to explore the influence of surface currents on the migratory route of juvenile sockeye salmon (smolts) through the Strait of Georgia. We used a model of downstream migration to generate daily numbers of Chilko Lake sockeye salmon smolts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 19 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…mainland coast with no stock-specific route preference (Groot and Cooke, 1987;Groot et al, 1989;Welch et al, 2009). Simulation models indicated that surface currents within the Strait affect the seaward migratory route of Fraser River sockeye smolts (Peterman et al, 1994). Prevailing northwest wind conditions in spring and early summer would force smolts along the eastern shore of the Strait.…”
Section: Juvenile Fraser River Sockeye Salmon Migration and Behaviormentioning
confidence: 99%
“…mainland coast with no stock-specific route preference (Groot and Cooke, 1987;Groot et al, 1989;Welch et al, 2009). Simulation models indicated that surface currents within the Strait affect the seaward migratory route of Fraser River sockeye smolts (Peterman et al, 1994). Prevailing northwest wind conditions in spring and early summer would force smolts along the eastern shore of the Strait.…”
Section: Juvenile Fraser River Sockeye Salmon Migration and Behaviormentioning
confidence: 99%
“…These results suggest that in winter, the effect of wind on the migration pattern of the Asian and East Kamchatkan chum salmon is greater than that on the North American chum salmon. Peterman et al. (1994) also suggested that the most important physical factor that influences the migratory route of juvenile sockeye salmon is the direction and strength of the surface winds during their early marine life stage.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling studies have been shown to be an appropriate method to investigate the influences of several factors upon salmon migration. Peterman et al. (1994) showed the influence of surface currents on the migratory routes of juvenile sockeye salmon ( O. nerka ) using a model that was coupled with a two‐layer hydrodynamic model.…”
Section: Introductionmentioning
confidence: 99%
“…Spatially explicit individualbased models (where spatial locations are included) have been used in fisheries oceanography to investigate the fate of eggs and larvae (e.g., Bartsch et al 1989;Davidson and deYoung 1995;Hermann et al 1996;Hinckley et al 1996) and in fish migration studies (e.g., Fiksen et al 1995). This methodology has been applied to study sockeye salmon both in the ocean (e.g., Dat et al 1995) and in estuaries (e.g., Peterman et al 1994). The method used for these spatially explicit models was to combine a hydrodynamic model (yielding current fields) with a model of larval or fish behaviour (tracking particles and adding behaviours).…”
Section: Introductionmentioning
confidence: 99%